Regulation of the mouse desmin gene: transactivated by MyoD, myogenin, MRF4 and Myf5. - Li, H (1993)
Desmin, the muscle specific intermediate filament (IF) protein, is expressed at low levels in myoblasts and at the onset of differentiation its expression increases several fold. In an effort to explore the mechanism involved in the tissue-specific and developmentally regulated expression of desmin, we have isolated the mouse desmin gene. Sequence analysis of 976 bp 5' flanking region revealed several potential cis-acting elements: 1) Three E boxes (MyoD binding sites), namely, E1, E2 and E3, located at -79, -832 and -936, respectively; 2) one MEF2 binding site at -864; 3) a region with homology to M-CAT motif at -587; 4) several GC boxes. Transient transfections with various 5' flank deletion mutants into C2C12 muscle cells have revealed both positive and negative elements that seem to be involved in the expression of desmin. The first 81 bp upstream of the transcription initiation site, including E1 box, were sufficient to confer muscle specific expression of the desmin gene. The maximal level of expression was achieved by the construct containing up to -897 base pairs. The region between -578 to -976 behaves as a classical enhancer in the absence of which the region between -578 and -81 suppresses CAT activity. Gel electrophoretic mobility shift assays using both C2C12 muscle cell nuclear extracts as well as in vitro translated myoD/E12 and myogenin/E12 heterodimers, showed that both myoD and myogenin bind to the proximal E1 and the distal E2 boxes of the desmin promoter and enhancer respectively. Co-transfection of myoD, myogenin, MRF4 and Myf5, with the desmin-CAT construct into 10T-1/2 cells demonstrated that all these factors could transactivate desmin gene expression.